Nature and Specificity of Effector Cells in Cell-Mediated Cytolysis of Mouse Adenovirus-Infected Cells - Inada, Toshiki (1978)
The type of effector cells in immune spleen cells (ISC) responsible for cell-mediated cytolysis of mouse adenovirus-infected cells was characterized. When ISC were pretreated with anti-mouse thymocyte or anti-Thy1.2 serum and complement, their cytolytic activity assayed by the (51)Cr release test was completely abolished, whereas it was not significantly reduced either when ISC were pretreated with anti-mouse immunoglobulin serum and complement or after ISC were kept standing at 37°C for 2 h in a plastic dish to remove adherent cells. These data indicate that the effector cells in ISC are T cells. The release of nonspecific or specific soluble cytotoxic factor(s) from ISC upon contact with mouse adenovirus-infected cells was not demonstrated, but about 30 U of interferon activity per ml was detected. However, 10 times as many units of exogenous interferon or more showed no effect on (51)Cr release from target infected cells or on the inhibition of viral antigen synthesis in infected cells. Experiments with mouse cells of different major histocompatibility antigens indicated that the cytotoxicity of ISC is effective when sensitizer and target cells share all or part of the same H-2 gene complex but not effective when they are of a different H-2 gene complex.